Urgently of Harmonization of National Legislation on Juvenile Criminal Justice Towards International Standards: A Review of Rules of Deprivation of Liberty of Child Offender - Antonius Ps Wibowo (UBL, 2013)
As a State Party to the Convention on the Rights of the Child (hereinafter: the CRCConvention), Indonesia is obliged to implement fully the Convention. For this purpose, Indonesiahas to undertake some measures, among others to undertake all appropriate legislative measuresfor the implementation of the rights recognized in the Convention. Legislative measures in thisregard include harmonization national legislation towards international standards.This paper aims to examine one problem, namely why harmonization of national legislationconcerning deprivation of liberty of child offender to international standards is urgent. This willbe answered by pointing out discrepancies between national legislation and internationalstandards based primarily on legal document analysis.Refer to the analysis, first reason for doing harmonization is current national legislation stilldiffers greatly from the CRC Convention. At one side, according to the CRC Convention, ruleson deprivation of liberty are: (1) deprivation of liberty shall be used only as a measure of lastresort; (2) deprivation of liberty shall be used for the shortest appropriate period of time; (3)States Parties ensure by strict legal provisions that legality of deprivation of liberty is reviewedregularly. At the other side, according to national legislation, especially Act no. 3 of 1997, ruleson deprivation of liberty are: (1) deprivation of liberty, includes pre-trial detention is possiblewhen a child has committed an offense punishable by a minimum sentence of five yearsimprisonment; (2) the maximum duration of deprivation of liberty is 175 days; (3) there is noprovision on reviewing regularly of deprivation of liberty.Second reason is Act no. 11 of 2012 that will eliminate Act no. 3 of 1997 and enter in to forceat July 2014 does also not conform to the CRC Convention. According to Act no. 11 of 2012,rules on deprivation of liberty are: (1) deprivation of liberty will not be used if child offenderguaranteed by parents or other relevant institution; (2) deprivation of liberty is unavoidable incase child offender has committed an offense punishable by a minimum sentence of seven yearsimprisonment and child has attained fourteen years old; (3) there is no provision on reviewingregularly of deprivation of liberty.Recommendation that should be carried out is to amend urgently the Act no. 11 of 2012 inlight of the CRC Convention